Advantages Of Internet Usage Among Final Year Diploma Nursing Students At Bestari University College, Setiu, Terengganu - Shamilah Abdul Kudus; Chan , Siok Gim (Asia Pacific Higher Learning Sdn Bhd., Lincoln University College, Malaysia, 2017)
Internet use has become very popular in education in recent years because it contains vast quantities of information that likely has a great impact on the student’s academic achievement. This study employed the survey method to explore individual students’ differences in Internet usage, impact on their general learning and improved English language skills. This is within the context of total time spent online during weekdays and weekends among 100 final year nursing students at Bestari University College, Setiu, Terengganu. The study also examined the relationship between Internet usage domains, Internet usage and socioeconomic status. Lastly the study ascertains the effect of Internet use on their academic performance. Results indicated that students used the Internet mainly because they perceived the Internet to be useful to their job tasks, secondarily it is enjoyable and lastly it had an impact on their general learning especially their English language skills. Findings demonstrated that while usefulness was consistently perceived higher among the older students for all usage domains, the younger students perceived more on enjoyment. The results revealed no significant gender differences in all four aspects of internet usage. Findings implied that both genders had equal rate of computer utility and possessed almost comparable knowledge about Internet usage and its potentials. In fact, Internet usage neither depends on students’ place of residence nor socioeconomic status. However Internet usage when perceived for learning purposes was closely associated to academic achievements.